2018
DOI: 10.1002/anie.201712365
|View full text |Cite
|
Sign up to set email alerts
|

Alkynes From Furans: A General Fragmentation Method Applied to the Synthesis of the Proposed Structure of Aglatomin B

Abstract: Furans are versatile synthons in organic chemistry. Described is a general method for transforming furans into alkynes by dual C-C double-bond cleavage. The reaction is proposed to proceed by sequential [4+2] cycloaddition between furan and singlet oxygen and a formal retro-(3+2) fragmentation of the endoperoxide intermediate. A wide array of furans, including those derived from sapogenins, are amenable to this reaction, thus providing the corresponding alkynoic acids in up to 88 % yields. The synthetic utilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Herein, we report that we have achieved a biomimetic synthesis of sarocladione in only two or seven steps from ergosterol, an inexpensive, commercially available sterol. The synthesis was enabled by the development of a novel ruthenium‐catalyzed endoperoxide fragmentation reaction, [8] which transformed the A/B/C tricyclic ring system of the classical steroids into 14‐membered macrocyclic diketones by cleavage of two C−C bonds. Moreover, the synthesis allowed us to unambiguously determine that the structure of sarocladione is in fact not 1 but 2 (Figure 1 A), as indicated by X‐ray crystallographic analysis.…”
Section: Figurementioning
confidence: 99%
“…Herein, we report that we have achieved a biomimetic synthesis of sarocladione in only two or seven steps from ergosterol, an inexpensive, commercially available sterol. The synthesis was enabled by the development of a novel ruthenium‐catalyzed endoperoxide fragmentation reaction, [8] which transformed the A/B/C tricyclic ring system of the classical steroids into 14‐membered macrocyclic diketones by cleavage of two C−C bonds. Moreover, the synthesis allowed us to unambiguously determine that the structure of sarocladione is in fact not 1 but 2 (Figure 1 A), as indicated by X‐ray crystallographic analysis.…”
Section: Figurementioning
confidence: 99%
“…This Synpacts article will highlight our recent development of an alkyne-forming furan fragmentation, which oxidizes furans with singlet oxygen to afford alkynoic acids as structurally distinct products. 8 The key to the success of this reaction is the introduction of ring strain 9 onto the furan ring via fusion with cycloalkanes.…”
Section: Syn Lettmentioning
confidence: 99%
“…Eventually,itwas found that partial reduction of the alkyne with the Lindlar catalyst, followed by palladium-catalyzed oxidative cyclization [27] could deliver aglatomin B (1)w ith good levels of diastereoselectivity.B arring some discrepancies between the NMR data of the synthetic sample and the natural isolate [11] (see the Supporting Information), the synthetic sample was ambiguously shown to possess the proposed structure of aglatomin Bb yX -ray crystallography. [32] In summary,t hrough au nique mode of endoperoxide fragmentation, asimple means to convert furans into alkynoic acids has been discovered. Thef uran first engages singlet oxygen to afford the Diels-Alder adduct 22, which could undergo either homolytic O À Oc leavage [29] (radical pathway) or retro-1,3-dipolar cycloaddition (ionic pathway) to furnish the anhydride 25 (see page S10 of the Supporting Information for am ore detailed analysis).…”
Section: Angewandte Chemiementioning
confidence: 99%